A Comparative Study of Freeway Space Measured in Dentulous Patient With and Without Head Stabilizing Device - Bhandari, Anamika; Thakur, Smriti Narayan; Sapkota, Srijana Mishra; Rajbanshi, Mahesh Kumar (Journal of Nepalese Prosthodontic Society, 2025)
Introduction: Freeway space is described as the space between the maxillary and mandibular teeth when the mandible is in the natural or physiological rest position. The incorrect measurement of freeway space can lead to bruxism of teeth, difficulties in creating the lip seal, artificial appearance, cheek biting, angular cheilitis, temporomandibular joint pain etc. The physiological rest position of themandible is widely used in clinical practice as a functional method for the determination of freeway space. However, the mandibular position is considered to be affected by various factors such as head and body postures. Thus, the purpose of this study is to determine and compare the average freeway space in dentate subjects with and without head stabilization.Methods: The total sample of 81 adult patients with the age range of 18-35 years were taken. Vertical dimension at rest and Vertical dimension at occlusion were measured with and without head stabilization and freeway space value was calculated. Paired sample t-test was used to compare the freeway space with head stabilization and without head stabilization.Results: The mean freeway space with head stabilization and without head stabilization was 2.7 + 1.25 mm and 2.52 + 1.32 mm respectively. There was no statistically significant difference in the freeway space with and without head stabilization.Conclusion: The freeway space in dentate adults range from 1-6 mm. There is no evidence to support that FWS values obtained after head stabilization is close to the recommended range of FWS compared to the values obtained without stabilizing head.